On the integrated production, inventory and preventive maintenance problem in manufacturing systems with backorder. (10th April 2010) - Kenne, Jean-Pierre; Gharbi, Ali; Najid, Najib M.
The integrated Production, Inventory and Preventive Maintenance Problem (PIPMP) is concerned with coordinating production, inventory and preventive maintenance operations to meet customer demand with the aim of minimising costs. The particular PIPMP considered in this paper involves the dynamics of an unreliable production environment that strongly depends on an age-dependent likelihood of machine breakdowns. We provide optimality conditions for more realistic manufacturing systems and use numerical methods to obtain the optimal preventive maintenance policy and the relevant age-dependent production policy. Compared with available production and preventive maintenance policies, the numerical solution obtained shows that the proposed age-dependent optimal production and maintenance policies significantly reduce the overall incurred cost.